In vivo study on biodegradable magnesium alloys: Bone healing around WE43 screws - Levorová, Jitka; Duskova, Jaroslava; Drahos, Milan; Vrbova, Radka; Vojtech, D; Kubasek, Jiri; Bartos, Martin; Dugová, Lenka; Ulmann, Dan; Foltan, Rene (Journal of biomaterials applications, 2018)
Introduction A standard osteosynthetic material for maxillofacial skeleton is titanium and its alloys. The convenience of degradable material is avoiding of second surgery in cases, where removal of the material is necessary. Magnesium biodegradable alloys have similar mechanic properties as cortical bone - reasonable corrosion and sufficient biologic properties. They might be used in facial skeleton fixation. Materials and methods The study included a total of 16 rabbits, and they were randomly divided into two groups. Each group received two screws (WE4 and titanium as a standard material) in artificially drilled defect into right tibia. Animals were euthanized at four-week intervals. Bone samples with implants underwent microfocus CT scans and were histologically examined. Results WE43 alloys showed fragmentation of the material on the 16th week - statistically significant volume loss was found between weeks 12 and 16. Bone healing around the WE43 screws was of similar quality as around titanium screws, and no adverse effect was noticed. Conclusion The study showed good quality of bone healing around WE43 implants. From this point of view, the WE43 alloy meets the requirements of osteosynthetic material for maxillofacial skeleton.
Keywords: Magnesium; Animals; hořčík; Rabbits; vstřebatelné implantáty; povrchové vlastnosti; kostní šrouby; Tibia; Titanium; titan; slitiny; Absorbable Implants; Male; Alloys; tibie; králíci; zvířata; mužské pohlaví; Surface Properties; Bone Screws